Overexpression of host furin protease and inhibitory activities of synthetic chalcones- and azepines- derivative compounds toward dengue virus type-2 / Khuzaidatul Azidah Ahmad Nazri - Ahmad Nazri, Khuzaidatul Azidah (2016)
The outbreak of dengue disease continues to occur despite extensive measures of vector control. Meanwhile, progress in the vaccine development is often affected by various challenges thus delaying in the production of an effective vaccine across all four dengue serotypes. Thus, efforts in combating dengue are being channelled to other alternatives such as dengue antivirals. The search for this therapeutics has given rise to various screening methods to test for potential inhibitory activities of purified as well as synthetic compounds. Therefore, one of the aims of this study is to produce a fiirin recombinant protein. This current study also aims to determine the inhibitory effect of the synthetic chalcones- and azepines-derivatives toward dengue virus infection in vitro. To achieve the first objective, the furin gene isolated from HepG2 cells inoculated with dengue virus type-2 (DENV2) was cloned and overexpressed in the E.coli. The protein lysates of the overexpressed protein were purified using Ni²⁺ (resin) affinity chromatography and its concentration was measured by Bradford assay. The purified furin was confirmed by SDS-PAGE and Western blot analysis. The result showed that the furin is expressed at 60 kDa and was positive toward Rabbit Monoclonal Anti-Furin antibody. Subsequently, two groups of synthetic chalcones (2446DA and 20H46DA) and azepines (MA13, MA15 and MA16) derivatives were measured for their inhibitory activities toward dengue infection by cytotoxicity assay, plaque assay, indirect immunostaining, in vitro inhibition assay and fluorescence scanning microscopy. The cytotoxicity assay results showed that the concentration below maximum non-toxic dose (MNTD) for both 2446DA and 20H46DA in HepG2 cells was 15 μg/mL. The same value was obtained for MA15 and MA16. However, MA13 was observed to be less toxic compared to all test compounds with MNTD of 30 μg/mL. The plaque forming unit per ml (pfu/m1) was reduced prominently by 10 to 1000 fold when the infected BHK21 cells were treated with the highest non-toxic concentration compared to lowest non-toxic concentration. The indirect immunostaining results showed a similar trend of virus particles reduction on infected HepG2 cells in both the chalcones- and azepines-derivatives when treated at simultaneous- and post- conditions. However, the azepines MA13 exhibited the most potent activity towards DENV2 whereby total inhibition of virus particles was observed during simultaneous-treatment condition. The in vitro inhibition assay results showed that at concentration below MNTD, all compounds exhibited inhibitory activity against DENV2 in a dose dependent manner, indicated by the absence of cytopathic effects. The inhibitory potency strength exhibited was between 73% to 100% against both 1000 TCID₅₀ (p>0.05) and 100 TCID₅₀ (p<0.05). Results of the fluorescence scanning microscopy showed that all cytoskeletal changes induced by DENV2 infection were managed by the inhibitory activity of chalconesand azepines-derivatives in BHK21 cells. In conclusion, we proposed that the purified furin host protease to have high substrate specificity and highly potential to be developed as screening tool for anti-furin compounds. More importantly, the synthetic chalcones- and azepines-derivatives are suitable candidates for the development of therapeutics against dengue infection.